EVALUASI AKURASI PERAMALAN PENJUALAN DENGAN METODE SEMI AVERAGE DAN LEAST SQUARE PT INDOFOOD SUKSES MAKMUR Tbk - Widianingrum, Enggar; Iwan Supriyanto (JMD : Jurnal Riset Manajemen & Bisnis Dewantara, 2025)
This study aims to analyze sales forecasting at PT Indofood Sukses Makmur Tbk. using the Semi Average and Least Square methods in order to identify historical sales patterns and measure prediction accuracy for the upcoming period. The research employs a descriptive quantitative approach with the population consisting of PT Indofood Sukses Makmur Tbk.’s financial statements for the period 2020–2024, while the sample is the net sales data taken from the company’s annual income statements. The analysis was carried out using the Semi Average and Least Square methods, with accuracy evaluated through Mean Squared Error (MSE) and Mean Absolute Percentage Error (MAPE). The results indicate that the Semi Average method produced an MSE value of 48,080,998,381.43 and a MAPE of 213.26%, while the Least Square method yielded an MSE of 6,971,891,696.24 and a MAPE of 66.67%. These findings suggest that the Least Square method provides a more representative forecasting model compared to the Semi Average method, although the overall forecasting accuracy remains relatively low. This research highlights the necessity of applying more advanced and adaptive forecasting models in the future to support more effective managerial decision-making.